Avaliação de efetividade de políticas públicas municipais promotoras da igualdade de gênero: o caso de Humaitá-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
This study aimed to evaluate the effectiveness and efficacy of public policies and governmental and non-governmental actions developed in the municipality of Humaitá-AM aimed at empowering women and girls. As far as the nature of the study is concerned, it is a descriptive documentary and exploratory study. As far as the procedures are concerned, it is a bibliographical, documentary, and exploratory field study. For the methodological procedures, a mapping of national, state, and municipal public gender policies and local and civil society initiatives was conducted to evaluate public policies and actions to promote gender equality in the municipality of Humaitá-AM. The continuous evaluation method of the National Regional Development Plan (PNDR) was applied, which aims to reduce regional inequalities and activate regional development potential in territories that are of less interest to market agents, valuing local diversities. This method can assess the evaluation cycle of public policies and their economic and social impacts and is also made up of four blocks of evaluations, which can be carried out over four years, which corresponds to the same planning period as the Multi-Year Plan (PPA), in the governmental and non-governmental spheres the period which corresponds to the planning of each president's administration. It also monitors the implementation and applicability of national, state, and municipal policy instruments and actions to promote gender equality, checking their effectiveness, efficiency, and continuity. Six (6) governmental institutions in the Municipality took part in the research, including some municipal secretariats and eight (8) non-governmental institutions, including associations: urban, rural, riverside and Indigenous. An ex-post analysis of the programs already implemented in the municipality was conducted, using six (6) social indicators and two (2) SDG5 targets on gender equality to assess the effectiveness of public policies. To this end, historical series were constructed with state and municipal indices for the period 2015 to 2021. Secondary data was obtained from social, economic, and environmental development monitoring systems, such as IBGE, IPEA, DATASUS, ATLAS ODS, SEMSA, TSE, Humaitá City Hall HR, the 4th Military Police Battalion and Humaitá CDL. The results presented concrete and measurable data on the evolution of women's achievements in the political field, with greater participation of women in commissioned positions, greater participation in elective positions for the municipal parliament. In the economic field, there has been greater participation by women in the various public bodies present in the municipalities, and in the social field, with greater participation by women in Humaitaense society, occupying management positions, such as president and members of associations. This indicates, to a certain extent, the effectiveness and efficiency of existing policies aimed at women in the municipality. However, there is still much to be done, due to the barriers, macho cultures and paradigms that need to be broken down and confronted, requiring greater female participation to build a full and equitable democracy in local and national societies.
Keywords: Direitos das mulheres; Igualdade; Mulheres - Política governamental - Humaitá (AM); CIENCIAS HUMANAS: CIENCIA POLITICA: POLITICAS PUBLICAS: ANALISE INSTITUCIONAL; Avaliação; ODS 5; Igualdade de gênero; Efetividade; Eficácia